Biochemical profile of paediatric adamantinomatous craniopharyngiomas: A prospective cohort study - Jokonya, Luxwell; Mduluza-Jokonya, Tariro Lavender; Esene, Ignatius; Mwale, Garikai; Thango, Nqobile Sindiswa; Mduluza, Takafira; Naicker, Thajasvarie (Frontiers in Surgery, 2022)
ABSTRACT Introduction: Craniopharyngioma is a rare brain tumour. Despite being histologically benign, it behaves aggressively and is often difficult to manage. Descriptive epidemiological data on the tumour is lacking in sub-Saharan Africa and there is none for Zimbabwe. The tumour usually has a cystic component that has been raising interest in the past decade. Few studies have looked at the biochemical composition thereof. This study aims to give a landscape view of craniopharyngiomas (CP) in Zimbabwe and then profile the biochemical properties of the cystic component of paediatric adamantinomatous craniopharyngioma. Methodology: A prospective cohort study was done in Zimbabwe over a 2 year-period to study the epidemiological distribution of craniopharyngioma and examine the biochemical composition of adamantinomatous craniopharyngioma cystic fluid in the paediatric population. Fifteen patients were recruited who had craniopharyngiomas, and of those, 9 paediatric adamantinomatous craniopharyngiomas had fluid analysed for biochemical components. SPSS statistical package was used to analyse the data. Descriptive statistics were used for epidemiological data. Results: The incidence of CP was calculated to be 0.53 per million person-years. Incidence amongst the paediatric population 0-14 years was 1.2 per 100 000-person years. Several biological components were found to be elevated significantly compared to serum and CSF. These are sodium, potassium, urea, alkaline phosphatase, phosphate, magnesium, albumin, Gamma Glutamyl Transferase (GGT), calcium, low-density lipids and glucose. Conclusion: The incidence of CP in Zimbabwe is similar to the rest of the world. Some biochemical components have been noted to be markedly elevated in the cystic fluid and were mirroring serum rather than CSF in concentration.